从美到责任: 自然的美学与环境伦理学 - Rolston, Holmes, 1932-2025, author; Chinese Social Science Publishing Co., publisher (Colorado State University. Libraries, 2009)
The environmental ethics of Rolston has caught more and more attention in recent years. In fact, his environment aesthetics is also worthy of attention, the environmental ethics and the environmental aesthetics, which are both going towards wilderness, are not separated from each other in his eyes. When the appreciation of beauty is changed from in - position viewing to participation or from outward form to historic depth, the relationship between environmental ethics and environmental aesthetics has been established and then beauty can go towards duty.
From beauty to duty: aesthetics of nature and environmental ethics
Cong mei dao ze ren: zi ran de mei xue yu huan jing lun li xue
Translated by Zhao, Hongmei.
Text in Chinese.
Keywords: scenic grandeur; environmental aesthetics; environmental ethics; duty; participation; beauty; conservation; biotic community; nature